Identification of key genes of hesperidin in inhibition of breast cancer stem cells by functional network analysis. (February 2021) - Hermawan, Adam; Khumaira, Annisa; Ikawati, Muthi; Putri, Herwandhani; Jenie, Riris Istighfari; Angraini, Sonia Meta; Muflikhasari, Haruma Anggraini
Graphical abstract: Highlights: A study on hesperidin-targeted BCSCs never yet performed. Combination of in silico and in vitro work. Target mining of hesperidin using bioinformatics. Validation of hesperidin target molecular using mammosphere. Identification of p53 as a key protein of hesperidin in inhibition of BCSCs. Abstract: Breast cancer therapy with classical chemotherapy is unable to eradicate breast cancer stem cells (BCSCs). Loss of p53 function causes growth and differentiation in cancer stem cells (CSCs); therefore, p53-targeted compounds can be developed for BCSCs-targeted drugs. Previously, hesperidin (HES), a citrus flavonoid, showed anticancer activities and increased efficacy of chemotherapy in several types of cancer in vitro and in vivo . This study was aimed to explore the key protein and molecular mechanism of hesperidin in the inhibition of BCSCs using bioinformatics and in vitro study. Bioinformatics analysis revealed about 75 potential therapeutic target proteins of HES in BCSCs (TH), in which TP53 was the only direct target protein (DTP) with a high degree score. Furthermore, the results of GO enrichment analysis showed that TH was taken part in the biological process of regulation of apoptosis and cell cycle. The KEGG pathway enrichment analysis also showed that TH is involved in several pathways, including cell cycle, p53 signaling pathway. In vitro experiment results showed that HES inhibited cell proliferation, mammosphere, and a colony formation, and migration in on MCF-7 3D cells (mammospheres). HES induced G0/G1 cell cycle arrest and apoptosis in MCF-7 cells 3D. In addition, HES treatment reduced the mRNA level of p21 but increased the mRNA level of cyclin D1 and p53 in the mammosphere. HES inhibits BCSCs in mammospheres. More importantly, this study highlighted p53 as a key protein in inhibition of BCSCs by HES. Future studies on the molecular mechanism are needed to validate the results of this study.